Fernand Braudel e as metamorfoses do tempo e do espaço : o conceito de geohistória em La Méditerranée et le monde méditerranéen à l’époque de Philippe II (1949 e 1966) - Guilherme Ribeiro (Confins)
This paper analyses the empirical and theoretical dimensions of the concept of geohistory in the two editions of the La Méditerranée et le monde méditerranéen à l’époque de Philippe II (1949 e 1966). Emphasizing his most uses, his relationship with the determinism and the influence of French and German geography, our objective is to show that geography has a crucial epistemological role in the braudelian historical writing.